Study on Malay reserved land in Kubang Pasu and Kota Setar / Nurul Aqilah Aizmi - Aizmi, Nurul Aqilah (2022)
Malay Reserve Land is land which was reserved only for alienation to the Malays only. It can only be transacted between the Malays. Transaction here includes sales and purchase of the land, transfer of title, mortgage and lease. There are various sections in Malay Reservation Enactment for Malay Reservation Land which has been enacted by the British. This land is restricted from sale, lease, transfer of title and mortgage to the non-Malays. However, the decreases of value Malay Reserve Land area are still happening until now. This is because there are several factors that contributed to the decreases of the land area. In Kedah for average, almost 147,071 hectares of Malay Reserve Land decrease from 2013 to 2018. From the figures, it in critical situation and if that Malay Reserve Land is not protected, it will eventually disappear the rights of Malay of the country. Therefore, this study is conducted to study, analyse and present the analysis of Malay Reserved Land categories in Kubang Pasu and Kota Setar. Through this research also, it organizes to identify the current issues involving Malay Reserve Land and also know location and value of Malay Reserve Land area by categories. In fact, through a preliminary study conducted, there were several current issues that caused the decreases in the area of Malay Reserve Land, which is land taken by the state authorities to build a public interest but do not replace land taken by the same value land. In addition, there are also several landowners who sell or lease their land to non-Malays. The data for this study was obtained through Department of Director General of Lands and Mines and Department of Survey and Mapping Malaysia (JUPEM). Then, data is analysed through qualitative methods using the latest technology, which is Geographical Information System. For overall of this study found that the difference to the industry area in Kubang Pasu and Kota Setar where the percentage of industrial is low and other percentage of land use of agriculture and building showed their rates are high. So, it hoped that with the identification of the decrease and some of the proposed Malay Reserve Land protection ways in this study will help the authorities to maintain and increase the value of land of rights Malays and for benefit in future.